Recent Advances of Fe–N–C Pyrolyzed Catalysts for the Oxygen Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J (Elsevier B.V., 2020)
This review summarizes recent advances in the development of pyrolyzed M–N–C catalysts for the oxygen reduction reaction, focusing on activity, stability, and the reactivity descriptors proposed for the rational design of pyrolyzed M–N–C catalysts. We discuss the last advances in achieving high catalytic activity and stability and the new insights into the characterization of FeN4 active sites by Mössbauer spectroscopy in combination with Density Functional Theory (DFT) calculations of the Fe–N–C catalysts. In addition, we present the different reactivity descriptors proposed in the literature for the rational design of Fe–N–C pyrolyzed materials: (i) structural descriptors determined by X-Ray Photoelectron Spectroscopy (XPS) and Mössbauer spectroscopy and (ii) the redox potential of the active center MNx. © 2020 Elsevier B.V.